An Analysis of a Textbook Entitled â€œStep into the English World: A Character-Based English Textbook for Junior High School Grade VIIIâ€ Used in the Teaching English at the Eight Grade Students of SMP Negeri 2 Singaraja - ., Wayan Cherrie Hana Melati; ., Drs.Gede Batan,MA; ., Ni Komang Arie Suwastini, S.Pd,M.Hum. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Perubahan kurikulum di Indonesia memberi dampak yang signifikan pada sistem pendidikan serta pengembangan materi. Kurikulum 2013 yang mendasari perkembangan buku teks dalam pendidikan di Indonesia terlibat dalam polemik. Meski demikian terdapat banyak penelitian tentang pengembangan bahan ajar berdasarkan kurikulum ini, khususnya buku teks. Sebagai contoh, buku berjudul â€œStep into the English World: A Character-based Textbook for Junior High School Grade VIIIâ€ yang dikembangkan oleh seorang mahasiswa dari Universitas Pendidikan Ganesha berdasarkan kurikulum 2013. Penelitian ini, sama halnya dengan penelitian sejenis terkait analisis buku teks bertujuan untuk mengetahui masalah yang guru dan siswa hadapi dalam pelaksanaan buku pelajaran, kualitas umum buku teks dan kesesuaiannya dengan penerapan kurikulum 2013. Penelitian ini menunjukkan bahwa buku teks yang berkualitas harus menekankan pada kelebihannya dan membatasi kekurangan berdasar teori Richards (2001). Selanjutnya, buku teks harus memenuhi kriteria buku teks yang baik untuk setiap aspek evaluasi yang tersaji pada checklist yang telah divalidasi oleh beberapa evaluator ahli. Temuan penelitian ini menentukan apakah buku teks yang dikembangkan berdasarkan kurikulum 2013 memiliki pengaruh yang signifikan terhadap masalah pelaksanaan pada kurikulum ini. Hasil penelitian ini akan membawa beberapa kontribusi yang signifikan terhadap perkembangan pendidikan di Indonesia secara umum, dan khususnya dalam pengembangan buku teks berdasarkan kurikulum 2013.Kata Kunci : kurikulum 2013, analisis buku teks, kualitas buku teks, checklist The curriculum reform in Indonesia gave a significant effect on the education system as well as the material development. Although the latest change into the Curriculum 2013 which provides the blue print for the development of the textbooks nationally in Indonesian education is caught in polemic, there are many books designed in accordance with this curriculum. One of the examples was a textbook entitled â€œStep into the English World: A Character-based Textbook for Junior High School Grade VIIIâ€ which was written by a student of Ganesha University of Education. The recent study was aimed at finding out the problems that the teacher and students encountered in the implementation of the textbook, the textbookâ€™s general quality and its suitability to the recently applied curriculum 2013. This research found out that there were still many problems in the implementation of the textbook, even though the textbookâ€™s general quality was classified as good and was relevant with the curriculum 2013. This study suggests that in order to bring out a quality textbook, the advantages of the textbook should be strengthened and the disadvantages should be limited. Furthermore, textbook should meet the criteria of good textbook for each the evaluated aspects presented on checklist which had been validated by some judges. The findings of this research will be significant in determining whether or not the textbook developed laid down by the curriculum 2013 contributes a significant effect to the current issues of the curriculum 2013 implementation problems. The result will bring out some significant contributions on the development of the Indonesian education in general, the textbook development in regard to the curriculum 2013 in particular.keyword : curriculum 2013, textbook analysis, quality textbook, checklist